Low Sleep Hygiene Is Associated with Less Adherence to the Mediterranean Diet in Chilean Schoolchildren from Rural Public Schools—A Cross-Sectional Study - Rafael Zapata-Lamana; Jessica Ibarra-Mora; Fernanda Carrasco-Marín; Samuel Durán-Agüero; Jorge Cuevas-Aburto; Maria Antonia Parra-Rizo; Igor Cigarroa (Children, 2023)
The Mediterranean diet stands as a widely acknowledged and health-promoting dietary pattern, renowned for its notable linkage to the mitigation of noncommunicable chronic maladies. Nonetheless, the existing body of evidence concerning the potential interrelation between sleep hygiene and this dietary regimen remains circumscribed. The main objective was to determine the association between sleep hygiene and adherence to the Mediterranean diet in Chilean schoolchildren from rural public schools in southern Chile. A non-experimental study was carried out, with an analytical, cross-sectional design. A total of 265 students (56.6% women, mean age 13.5 ± 1.8) from a rural community in southern Chile were recruited. Sleep habits were evaluated using Section 6 of the Life Habits and Adolescence Questionnaire, Sleep and Rest, and adherence to the Mediterranean diet was assessed with the KIDMED Mediterranean Diet Adherence Questionnaire. The main results indicated that 52.8% of schoolchildren need to improve adherence to the Mediterranean diet and 16.6% have a low-quality Mediterranean diet. A high percentage of schoolchildren have behaviors related to poor sleep hygiene (going to bed late (46%), waking up tired and wanting to continue sleeping (63.8%), and having problems falling asleep (42.6%)). Schoolchildren who got up after 8:30 a.m., those who fell asleep after midnight, upon conducting a comparative analysis of the students based on their sleep patterns, those who woke up tired and those who had trouble falling asleep had a lower level of adherence to the Mediterranean diet compared to schoolchildren who got up earlier than 8:30 a.m., fell asleep before midnight, did not wake up tired, and those who did not find it difficult to fall asleep, respectively. In conclusion, having poor sleep patterns including difficulties in both awakening and falling asleep are associated with less adherence to the Mediterranean diet in schoolchildren from rural public schools in southern Chile. Monitoring these variables and promoting healthy lifestyle habits within the educational community are essential measures.